2017
DOI: 10.11591/edulearn.v11i3.6410
|View full text |Cite
|
Sign up to set email alerts
|

Concept Acquisition of Rotational Dynamics by Interactive Demonstration and Free-Body Diagram

Abstract: The concepts of force and motion are essential material in physics. However, students experience many difficulties in the concept of force in rotational dynamics. This research was conducted to measure students' concept acquisition of the rotational dynamics through Interactive Demonstration assisted by Free-body diagram. The mixed research method was chosen through the use of test instruments in the forms of 10 multiple-choice with open ended questions. The subjects of the research were 35 students XI IPA Sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Vector addition and subtraction in the questions use a visual representation in the form of arrows. The length and direction of the arrows become crucial indicators in determining accuracy in vector operations (Pranata & Lorita, 2023). Student responses are converted into quantitative data based on a modified rubric, as shown in Table 2.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Vector addition and subtraction in the questions use a visual representation in the form of arrows. The length and direction of the arrows become crucial indicators in determining accuracy in vector operations (Pranata & Lorita, 2023). Student responses are converted into quantitative data based on a modified rubric, as shown in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…The length of arrow or magnitudes of both vectors remain the same, only the second vector has the opposite direction. Studies on students' abilities to operate arrows become crucial to emphasize in learning, especially in physics (Pranata & Lorita, 2023).…”
Section: Descriptive Statistic and Checking Assumptionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The analysis of their questionnaire data indicated that there was no statistically significant difference in the responses of male and female learners, in relation to previously examined concepts. Pranata, et al (2017) examined the degree of Senior High School students' understanding of the concepts of rotational movement with the help of an interactive simulation, assisted by a free body diagram (Tanang et al, 2014), a questionnaire and a worksheet, specifically designed for it. Among other things, the researchers came into the conclusion that students: found it difficult to define the concept of force in complex rotating systems, tended to believe that the upward force usually has a positive torque and, vice versa, and knew that the moment of inertia of an object is affected by its mass and radius but found it difficult to refer to this.…”
Section: Introductionmentioning
confidence: 99%